An approach to financial valuation methodologies: bibliometric analysis and systematic review of the literature - Lopez-Rodriguez, Campo Elias; Velasquez-Lizcano, Carolina; Fajardo-Sierra, Jenny Marcela; Sierra-Otalora, Jenny Lucero (RAN - Revista Academia & Negocios, 2023)
Purpose: To develop an approach to financial valuation methodologies as a tool that allows managers to have an objective and decisive vision to generate business value. Methodology: A bibliometric analysis was conducted on Scopus indexed research articles using R Core Team 2022-Bibliometrix and VOSviewer software, and a systematic literature review adhering to the PRISMA protocol. Findings: The main methodologies for financial valuation include cash flows, real options, net present value, valuation by multiples, economic value added, and various complementary financial ratios. Practical implications: It is evident that there is a shortage of literature on the subject, despite that fact a consistent growth was observed. Originality: Financial valuation methodologies enable managerial decision-making associated with company valuation for long-term benefit.